PERAN PEMERINTAH DESA DALAM MEMBANGUN SUMBER DAYA MANUSIA DI DESA PEDANGKAMULYAN KECAMATAN BOJONGGAMBIR KABUPATEN TASIKMALAYA - Wasdi Wasdi (Jurnal Indonesia Sosial Sains, 2022)
The Village Government has a vital role in development but there are still many problems that occur including, in its administration there are problems with the role of the village government, especially in empowering the community, there is a lack of integration and synergistic relationships between village officials and the community, as well as village heads and village officials, the pros and cons of the program. village head, this affects the running of the role of the village. The purpose of this study was to determine the role of the village government in carrying out the development of Human Resources (HR) in the Village of Swordsmen, District of Bojonggambir, District of Tasikmalaya. This study uses a qualitative approach, with data collection techniques, informants, interviews, literature studies and field observations. The collected data is processed through data reduction, presentation of verification data and drawing conclusions. The results of this study indicate that the role of the village government as a motivator, facilitator, dynamist, stabilizer, innovator and pioneer has been running but still requires consistent improvement. This requires a synergistic relationship between the village government and the community. For the development of human resources from the physical aspect, it is still low because there are still health facilities and the feasibility of living for the community that cannot be fulfilled, from the intellectual aspect it is still said to be lacking, because of the lack of schools in the village of Swordsmen and the psychological on the spiritual basis of the community's religion is quite high, it is proven with religious activities the community has shown a good direction.